Impacto de las estrategias de marketing digital para promover la inclusión financiera en Lima Metropolitana - Carreño Leyton, Miguel Alberto (2022)
The present study aims to determine the impact of digital marketing strategies on the development of financial inclusion in Lima Metropolitana. Financial inclusion is one of the main problems in our country, this is a pillar that reduces poverty and contributes to economic and financial development, as well as bringing with it the economic prosperity of Lima households. The benefits of greater financial inclusion lie in the greater participation of citizens in the financial system, reduction of informality and lower costs. The increase in the use of the internet is increasingly significant. For this reason, different companies have been adapting to change, having a greater presence through digital media, in order to stay close to their customers and build loyalty. This does not exclude financial entities, since they are the ones that implement digital marketing strategies, taking into account that advertising actions through digital channels are called digital marketing. According to financial inclusion, these actions are strategies that promote that more people can join banking and can make use of banking products and services. Information was collected through population surveys and interviews with specialists on the subject. There is a large percentage of people who do not follow the financial institutions to which they are affiliated on social networks, however, the people who are affiliated are because they stay informed and the relevance of the content published by banks on social networks persists. Finally, when comparing research and the information obtained, it can be seen that financial institutions are not significantly present in digital media. In addition, mobile banking is the channel that has the most weight today, given the current context, and above all the lack of savings and mistrust is a reason why people are not affiliated with banking.